2019
DOI: 10.1002/cssc.201901799
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Polyurethane Elastomer‐Based Gel Polymer Electrolytes for Sodium‐Metal Cells with Enhanced Cycling Performance

Abstract: Sodium batteries have been recognized as a promising alternative to lithium‐ion batteries. However, the liquid electrolyte used in these batteries has inherent safety problems. Polymer electrolytes have been considered as safer and more reliable electrolyte systems for rechargeable batteries. Herein, a thermoplastic polyurethane elastomer‐based gel polymer electrolyte with high ionic conductivity and high elasticity was reported. It had an ambient‐temperature ionic conductivity of 1.5 mS cm−1 and high stretcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Impressively, it is revealed that the overpotentials of Na||ETPTA–NaClO 4 –QSSE||Na symmetrical cells are only 70, 151, 232, 254, 310, and 355 mV with increasing current densities of 0.1, 0.2, 0.4, 0.6, 0.8, and 1 mA cm −2 , respectively. Notably, the maximum withstand current density of ETPTA–NaClO 4 –QSSE is much higher than those of recently reported works, such as PEO‐based electrolyte (0.1 mA cm −2 ), [ 37,52 ] Na 3 Zr 2 Si 2 PO 12 (0.25 mA cm −2 ), [ 16–53 ] Na 3 SbS 4 (0.1 mA cm −2 ), [ 54,55 ] Na 2 S–P 2 S 5 (0.013 mA cm −2 ), [ 56 ] thermoplastic polyurethane‐based electrolyte (0.5 mA cm −2 ), [ 57 ] PVDF–HFP based electrolyte (0.5 mA cm −2 ) [ 58 ] (Table S1, Supporting Information). Furthermore, such low overpotential can be readily restored to 64 mV after the current density reduces back to 0.1 mA cm −2 , suggestive of excellent rate capability.…”
Section: Figurementioning
confidence: 99%
“…Impressively, it is revealed that the overpotentials of Na||ETPTA–NaClO 4 –QSSE||Na symmetrical cells are only 70, 151, 232, 254, 310, and 355 mV with increasing current densities of 0.1, 0.2, 0.4, 0.6, 0.8, and 1 mA cm −2 , respectively. Notably, the maximum withstand current density of ETPTA–NaClO 4 –QSSE is much higher than those of recently reported works, such as PEO‐based electrolyte (0.1 mA cm −2 ), [ 37,52 ] Na 3 Zr 2 Si 2 PO 12 (0.25 mA cm −2 ), [ 16–53 ] Na 3 SbS 4 (0.1 mA cm −2 ), [ 54,55 ] Na 2 S–P 2 S 5 (0.013 mA cm −2 ), [ 56 ] thermoplastic polyurethane‐based electrolyte (0.5 mA cm −2 ), [ 57 ] PVDF–HFP based electrolyte (0.5 mA cm −2 ) [ 58 ] (Table S1, Supporting Information). Furthermore, such low overpotential can be readily restored to 64 mV after the current density reduces back to 0.1 mA cm −2 , suggestive of excellent rate capability.…”
Section: Figurementioning
confidence: 99%
“…[ 16–23 ] Applications of Li metal anode have been hindered by the scarcity and uneven distribution of Li resource. Benefiting from the wide distribution of Na resource, it is possible to design high power, high energy density and low‐cost sodium‐based batteries by “enhanced cathode materials,” [ 24 ] “electrolyte design” [ 25 ] and sodium metal anode protection.…”
Section: Introductionmentioning
confidence: 99%
“…With our polyHIPEs we achieve a MacMullin number of less than 2, unmatched by any other stretchable separator technology. [ 8–10,40–48 ] Introducing potassium hydroxide (KOH) as electrolyte boosts the separator conductivity to record high 0.39 ± 0.05 S cm −1 while keeping the MacMullin number below 2, corroborating the performance increase achievable with polyHIPE separators.…”
Section: Figurementioning
confidence: 84%